Clinical nursing skills : core and advanced - Cooper, Simon , 1967-; Endacott, Ruth; Jevon, Phil (New York : Oxford University Press, 2009)
Designed as a compelling text for students, 'Clinical Nursing Skills' offers evidence-based, practical guidance for procedures in all settings. Emphasis is placed on the development of decision-making and problem-solving skills
1. Communication skills -- 2. The patient pathway -- 3. Essential skills -- 4. Drug administration -- 5. Cardiovascular system -- 6. Respiratory system -- 7. Neurological system -- 8. Renal system -- 9. Gastrointestinal system -- 10. Musculoskeletal system
Includes bibliographical references and index
Keywords: Nursing; Nursing Care; Clinical competence; Nursing assessment